Polymorphic thymidylate synthase gene impacts on overall survival of patients with epithelial ovarian cancer after platinum-based chemotherapy. (November 2012) - Biason, Paola; Visentin, Michele; Talamini, Renato; Stopar, Alex; Giorda, Giorgio; Lucia, Emilio; Campagnutta, Elio; Toffoli, Giuseppe
Aim: High levels of TS have been associated with a worse clinical outcome in several cancers including epithelial ovarian cancer (EOC). The TS gene ( TYMS ) is highly polymorphic and has an effect on mRNA/protein expression.Materials & methods: Six TYMS polymorphisms were investigated for overall survival (OS) in 216 EOC patients: TYMS 1494ins/del, TSER (variable number of tandem repeats of 28 bp), TSER G>C, TYMS 1053C>T, TYMS IVS6-68C>T and TYMS 1122A>G.Results: In a multivariate analysis, TYMS 1494 del/del genotype was associated with a significant increased OS compared with the ins/ins genotype (hazard ratio: 0.36; 95% CI: 0.16–0.82, p = 0.01). Similar results were obtained for the mutant genotypes TYMS 1053TT and TYMS IVS6-68TT. The event-free survival was significantly higher in TYMS 1053TT patients compared with wild-type patients (p = 0.05).Conclusion: TYMS 1494ins/del, 1053C>T and IVS6-68C>T polymorphisms can be prognostic markers for OS in patients with EOC, independently from stage at diagnosis, median age and tumor histotype. Original submitted 11 May 2012; Revision submitted 10 August 2012